Vibrations: women in sound art, 1980-2000 - Ouzounian, G (Cambridge University Press, 2024)
From 31 October to 12 December 2015, Rumpsti Pumsti, a record store in Berlin devoted to experimental music and sound art, hosted an exhibition of early works by the German artist Christina Kubisch (b. 1948), one of the world’s foremost sound artists. The Vibrations exhibition focused on a series of works titled Dirty Electronics that Kubisch created between 1975 and 1980 in which she paired orchestral instruments with vibrators. On the floor were four wooden boxes each holding one flute and one vibrator, creating a jittery, buzzing flute quartet. Mounted on one wall was a photograph of a cello with a vibrator held to its strings. On another were technical diagrams. Kubisch, best known for her works with electronics, had produced intricately detailed diagrams of how to construct and use vibrators in various musical settings.